Mild reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant: First case report from Indonesia - Isnaini, Naniek; Mardian, Yan; Lokida, Dewi; Budiono, Fajar; Butar-butar, Deni P.; Arlinda, Dona; Salim, Gustiani; Kosasih, Herman; Wulan, Wahyu Nawang; Perodin, Jacqueline; Neal, Aaron; Lane, H. Clifford; et al. (Frontiers in Medicine, 2022)
Background: Reinfection with SARS-CoV-2 has been well documented, yet little is known about the degree of protection a previous infection provides against reinfection, especially against Variants of Concern (VOC). Case Presentation: Here we describe a case of an unvaccinated 49-year-old man who experienced two sequential SARS-CoV-2 infections with two different variants, as evidenced by genomic sequencing. The first episode was caused by the Pango lineage B.1.466.2 and resulted in severe COVID-19 with five days in an intensive care unit (ICU). The second episode approximately 6 months later, during the Delta surge in Indonesia. Genomic analysis showed that the second infection was caused by the Delta variant (Pango lineage B.1.617.2) and resulted in mild disease that did not require hospitalization. No SARS-CoV-2 nucleic acid was detected between the two episodes, but both binding and neutralizing antibodies to SARS-CoV-2 were detected prior to the reinfection, with the second infection leading to an increase in the levels of antibody. Conclusion: We confirmed that the patient experienced a reinfection instead of persistent viral shedding from the first infection based on epidemiological, clinical, serological, and genomic analyses. Our case supports the hypothesis that SARS-CoV-2 reinfection may occur once antibody titers decrease or following the emergence of a new variant. The milder presentation in the patient’s second infection deserves further investigation to provide a clear picture of the role of post-infection immunity in altering the course of subsequent disease.